Contribution of livestock to CO2 emission in SAARC countries: an empirical analysis of panel data - Khatri, Bishnu Bahadur; Poudel, Omkar; Acharya, Pradeep (International Journal of Environment, 2024)
This study investigates the contribution of livestock production to CO2 emissions in SAARC countries from 1990 to 2020 through an empirical analysis using panel data. The study included variables such as CO2 emissions and stocks, namely cattle, chickens, and goats. Data for the Maldives were excluded due to unavailability, and swine population data were also omitted for the same reason. Unit root tests revealed that the series were non-stationary at levels but became stationary after first differencing. The ARDL bounds test with a lag length of 3 (AIC = -7.951, SC = -7.060, HQ = -7.590) identified significant long-run relationships. Specifically, cattle (coefficient = 2.948, p-value = 0.000) and chickens (coefficient = 2.369, p-value = 0.000) were positively associated with CO2 emissions, while goats showed a negative association (coefficient = −5.594, p-value = 0.000). It was proven that there was a long-term equilibrium by cointegration tests like the Kao Residual cointegration test (ADF t-Statistic = -1.646, p-value = 0.049) and the Johansen Fisher panel cointegration test (Trace test and Max-Eigen test: p-value < 1%). Cross-sectional analysis revealed variability, with Afghanistan’s cointegration coefficient at -0.325 (p-value = 0.000) and Bhutan’s at 0.034 (p-value = 0.000). The results showed notable variability across countries, suggesting the need for tailored mitigation strategies. The study highlights the significant role of livestock in greenhouse gas emissions and calls for improved management and regional collaboration to mitigate environmental impacts in SAARC countries.